Penerapan Model Discovery Learning Dalam Pembelajaran Matematika Siswa Kelas X IPA SMA Negeri 2 Tana Toraja - Karismamega Toding Komnba' Paonganan (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
The application of discovery learning model is a learning that emphasizes students to findand discover for themselves about the material provided where the teacher only acts asa facilitator in the learning process. This study aims to describe the implementation oflearning, student activities and student learning outcomes in the application of discoverylearning models in mathematics learning for students of class X Science 1 of SMA Negeri 2TanaToraja on the subject of trigonometry. The population of this research is all studentsof class X IPA of SMA Negeri 2 TanaToraja. The research sample was students of ClassX Science 1 consisting of 25 students taken by cluster random sampling. The research datawas taken using: (1) observation sheet of the implementation of learning, (2) observationsheet of student activity, (3) student test results. In this study using a pre-experimentalresearch design without control, which means this study does not compare two treatmentsin two different groups, but only gives one type of treatment to the group that is discoverylearning models on trigonometry. It can be concluded that the implementation of learningis able to solve all stages of learning well with an average score of 3.73. Student activitiesare classified as active in participating in all learning activities with the discovery learningmodel with an average score of 85%. Student learning outcomes after applying the discoverylearning model on trigonometry can be stated thoroughly with an average completeness of75.60.